Strontium Ions Release from Novel Bioactive Glass-Containing Glass Ionomer Cements: A Preliminary Study - Albeshti, Rawan (Khalij-Libya Journal of Dental and Medical Research, 2024)
This study was conducted to measure the release of strontium ions that leached-out from novel bioactive glass-containing glass ionomer cements and also to evaluate effect of adding bioactive glass particles in various percentages on the strontium rate at different intervals. A series of ionomer glasses were synthesised based on 4.5SiO2-3Al2O3-0.75P2O5-3(CaO/SrO)-2(CaF2/SrF2) systems with varying strontium substitution from 0%Sr to 100%Sr. The cement discs were prepared with incorporation of sodium-free bioactive glass via substitutional basis and then were immersed in 10 ml of artificial saliva. After certain periods ranged from 7 days up to 28 days, the discs were collected and solution was analysed using inductively coupled plasma optical emission spectroscopy in order to obtain the cumulative release of strontium ions. Strontium ions release increased with increasing in strontium for calcium substitution, particularly during the first week of immersion. The highest strontium release was obvious from the fully strontium-substituted compositions. However, the strontium rate decreased with increasing in addition of bioactive glass at all time points. A substantial variation in strontium concentrations in the surrounding media was clearly observed with increasing both strontium and bioactive glass amounts in the parent glasses/cements. An extended work should be done to identify the optimal concentrations of strontium and bioactive glass that could combine together to manufacture an ideal bioactive material for dental applications. أجريت هذه الدراسة لقياس إطلاق أيونات السترونتيم التي تتسرب من الإسمنت الأيوني الزجاجي الحديث التصنيع وأيضا لتقييم تأثير إضافة الزجاج النشط بيولوجيا بنسب مختلفة وعلى فترات مختلفة. تم تصنيع سلسة من الزجاج الأيوني مع استبدال السترونتيم بنسب متفاوتة من 0 إلى 100. تم تحضير أقراص الإسمنت مع دمج الزجاج النشط بيولوجيا الخالي من الصوديوم وغمرها في 10 مل من محلول اللعاب الصناعي؛ لفترات زمنية مختلفة من 7 أيام إلى 28 يوم. بعد ذلك، تم جمع الأقراص وتحليل المحلول بواسطة جهاز التحليل الطيفي للبلازما للحصول على التسريب التراكمي لأيونات السترونتيم. زاد إطلاق أيونات السترونتيم مع زيادة نسبة السترونتيم المستبدل للكالسيوم خاصة خلال الأسبوع الأول من الغمر. تم الحصول على أعلى إطلاق للسترونتيم من التركيبات المستبدلة بالكامل بالسترونتيم. مع ذلك، انخفض معدل إطلاق أيونات السترونتيم مع زيادة نسب الزجاج النشط بيولوجيا. لوحظ وجود تباين كبير في تراكيز السترونتيم في الوسائط المحيطة مع زيادة كل من السترونتيم والزجاج النشط بيولوجيا في الزحاج/الإسمنت الأم. ينبغي القيام بتجارب موسعة لتحديد التراكيز المثلى من السترونتيم والزجاج النشط؛ مما يُسهم في تصنيع مادة نشطة مثالية لتطبيقات طب الأسنان